Reactivity controlled compression ignition: An advanced combustion mode for improved energy efficiency - Dalha, I.B. (Springer Singapore, 2019)
This chapter reviews reactivity controlled compression ignition (RCCI), which is an advanced combustion mode. RCCI is capable of improving thermal efficiency and reducing nitrogen oxides (NOx) and soot emission. However, it has high specific fuel consumption, unburned hydrocarbon (UHC) and carbon monoxide (CO) emissions, and thus requiring appropriate strategies. The effects of some strategies were found to influence advanced combustion phase and reduced UHC and CO emissions to a certain extent while maintaining RCCI reputability or otherwise. The use of bio-based low reactivity fuels (LRF) in RCCI combustion serves as a substitute for gasoline in reactivity stratification. Depending on the LRF used, utilization of biodiesel enables controlled combustion phase, extended load and significantly reduce soot and CO emissions, but it increases NOx and UHC emissions through NOx is compromised with biodiesel blends. The use of biodiesel can serve a greater advantage over conventional diesel when appropriate LRF and strategy are used especially for medium to higher blends or pure biodiesel. Â© Springer Nature Singapore Pte Ltd. 2020.